2012
DOI: 10.1093/jb/mvs119
|View full text |Cite
|
Sign up to set email alerts
|

Nucling, a novel protein associated with NF-κB, regulates endotoxin-induced apoptosis in vivo

Abstract: Nucling is a proapoptotic protein that regulates the apoptosome and nuclear factor-kappa B (NF-iB) signalling pathways. Strong stimuli, such as Gramnegative bacterial lipopolysaccharide (LPS), induce the simultaneous secretion of cytokines following the activation of NF-iB. Proinflammatory cytokines can induce liver damage through several mechanisms such as increases in oxidative stress and apoptotic reactions leading to tissue necrosis. Herein, we show that Nucling-knockout (KO) mice are resistant to LPS that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…EGFR signaling is required for estrogen-stimulated macrophage infiltration in the development of mammary tumorigenesis [ 48 ]. UACA is a proapoptotic protein that regulates NF-κB signaling [ 49 ], the expression of which is high in various cancers, including hepatocellular carcinoma [ 50 ]. KRT8 expression is high in patients with advanced liver fibrosis [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…EGFR signaling is required for estrogen-stimulated macrophage infiltration in the development of mammary tumorigenesis [ 48 ]. UACA is a proapoptotic protein that regulates NF-κB signaling [ 49 ], the expression of which is high in various cancers, including hepatocellular carcinoma [ 50 ]. KRT8 expression is high in patients with advanced liver fibrosis [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there is some evidence that the uveal autoantigen with coiled-coil domains and ankyrin repeats (UACA)/nucling may be involved in this translocation [60]. It has been shown that UACA/nucling is associated with canonical NF-κ signaling pathway [61-63] and was described as a functional regulator of sensitivity to extracellular inducers of apoptosis in cancer cells [64]. …”
Section: Introductionmentioning
confidence: 99%
“…Protein concentrations were determined using the BCA TM Protein Assay Kit (Pierce). Western blotting was performed as described previously (26). The following antibodies were used: anti-mouse middle portion of Nucling (m.Nucl.mid) (16); a phospho-NF-B-p65 (Ser-468) antibody (Cell Signaling); a phospho-STAT3 (Tyr-705) mouse antibody (Cell Signaling); caspase-3 antibody (Santa Cruz); a STAT3 antibody (sc482 Santa Cruz); anti-liver Arginase antibody (ab91279, Abcam); monoclonal anti-␤-actin (catalog number A5441, Sigma); HRP anti-mouse IgG (catalog number NA9310, GE Healthcare); and HRP anti-rabbit IgG (catalog number NA934, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%